Nucleic Acid Testing to Detect HBV Infection in Blood Donors - Stramer, Susan L; Wend, Ulrike; Candotti, Daniel; Foster, Gregory A; Hollinger, F. Blaine; Dodd, Roger Y; Allain, Jean-Pierre; Gerlich, Wolfram (The New England journal of medicine, 2011)
In this study involving 3.7 million blood donors, nucleic acid testing identified 9 donors with HBV infection who were not identified by routine serologic testing. The single triplex assay also identified 2 donors with HIV and 15 with HCV. The transfusion of blood containing hepatitis B surface antigen (HBsAg) is associated with post-transfusion infection with hepatitis B virus (HBV). Blood that is free of HBsAg but has high-titer antibodies against hepatitis B core antigen (anti-HBc) in the absence of antibodies against hepatitis B surface antigen (anti-HBs) can also transmit HBV infection. 1 , 2 In 1986, screening for anti-HBc was implemented in the United States to reduce HBV transmission and as a surrogate marker for non-A, non-B hepatitis (i.e., hepatitis C virus [HCV]). 3 , 4 However, a small proportion of donors with anti-HBc in the absence of HBsAg have circulating HBV DNA . . .